THE NEED ANALYSIS OF ENGLISH COURSE MATERIALS AT UNIVERSITY OF WIDYA DHARMA PONTIANAK - Paulina Erawati Paramita (JISOS: JURNAL ILMU SOSIAL, 2022)
English is one of the subjects listed in the UWDP curriculum and is required of all students in Management study program to take. Need analysis is used to select teaching materials because it is the process of gathering information about students' needs based on necessities, lacks, and wants. The purpose of this study was to examine the English needs of UWDP students. The need analysis results will be useful in English for English course in order to meet specific needs of learners and are related in content that is in its theme and topics to specific disciplines, occupations, and activities. The research method is a survey, and the research instrument is questionnaires. According to research findings, students' needs 1) Teaching material is integrated with language skills; 2) learning is more focused on language skills; and 3) teaching material is related to students' field of interest and preparation for work or professional lives